Lifestyle, sick leave and work ability among Norwegian employees with asthma—A population-based cross-sectional survey conducted in Telemark County, Norway - De Bortoli, Marit Müller (PLoS One, 2020)
OBJECTIVE: To investigate whether physician-diagnosed asthma modifies the associations between multiple lifestyle factors, sick leave and work ability in a general working population. METHODS: A cross-sectional study was conducted in Telemark County, Norway, in 2013. A sample of 16 099 respondents completed a self-administered questionnaire. We obtained complete data on lifestyle, work ability and sick leave for 10 355 employed persons aged 18–50 years. We modelled sick leave and work ability using multiple logistic regression, and introduced interaction terms to investigate whether associations with lifestyle factors were modified by asthma status. RESULTS: Several lifestyle risk factors and a multiple lifestyle risk index were associated with sick leave and reduced work ability score among persons both with and without physician-diagnosed asthma. A stronger association between lifestyle and sick leave among persons with asthma was confirmed by including interaction terms in the analysis: moderate lifestyle risk score * asthma OR = 1.4 (95% CI 1.02–2.1); high lifestyle risk score * asthma OR = 1.6 (95% CI 1.1–2.3); very high lifestyle risk score * asthma OR = 1.6 (95% CI 0.97–2.7); obesity * asthma OR = 1.5 (95% CI 1.02–2.1); past smoking * asthma OR = 1.4 (95% CI 1.01–1.9); and current smoking * asthma OR = 1.4 (95% CI 1.03–2.0). There was no significant difference in the association between lifestyle and work ability score among respondents with and without asthma. CONCLUSIONS: In the present study, we found that physician-diagnosed asthma modified the association between lifestyle risk factors and sick leave. Asthma status did not significantly modify these associations with reduced work ability score. The results indicate that lifestyle changes could be of particular importance for employees with asthma.